Beyond EPO - Corrigan, B. (Clinical Journal of Sport Medicine, 2002)
The objective of this review is to examine newer compounds coming on the market capable of boosting red blood cell concentration and thus improving aerobic activities in particular. Erythropoietin (EPO) has been used extensively in the past by the athletic community in this role. Its main disadvantages are the side effects due to increased viscosity, and the recent development of a blood test for drug testing methods. Two new methods of increasing red blood cell concentration for use in medicine are hemoglobin oxygen carriers and perfluorocarbons, each having a different structure, but which allow oxygen to be delivered to the tissues. Hemoglobin oxygen carriers physically alter the hemoglobin molecule by several methods so that complications such as renal toxicity are obviated. Perfluorocarbons belong to a group of synthetic compounds containing hydrocarbons to which fluorine is added. Evidence is available to suggest that athletes are already adapting these newer molecules for their benefit.